Selenoprotein T deficiency alters cell adhesion and elevates selenoprotein W expression in murine fibroblast cells - Sengupta, Aniruddha (2009)
Mammalian selenoproteins have diverse functions, cellular locations, and evolutionary histories, but all use the amino acid selenocysteine (Sec), often present in the enzyme’s active site. Only about half of mammalian selenoproteins have been functionally characterized, with most being oxidoreductases. The cellular role of selenoprotein T (SelT), manifesting a CxxU motif in a thioredoxin-like fold and localized to Golgi and the endoplasmic reticulum, is not known. To examine its biological function, we knocked down SelT expression in mouse fibroblast cells and found that SelT deficiency alters cell adhesion and enhances the expression of several oxidoreductase genes, while decreasing the expression of genes involved in cell structure organization, suggesting the involvement of SelT in redox regulation and cell anchorage. Furthermore, we found that the loss of SelT elevates expression of another selenoprotein, selenoprotein W (SepW1). SelT and SepW1 belong to the same protein family, suggesting that SepW1 may functionally compensate for SelT.